Analisis Strategi Peningkatan Kualitas Pelayanan pada PT. BPRS Jam Gadang Bukittinggi - Mia Yolanda; Yuwarman Mansur (ARZUSIN, 2026)
Although service quality in Islamic banking has been widely studied, research specifically analyzing strategies for improving service quality at Sharia Rural Banks based on the five SERVQUAL dimensions remains relatively limited. PT BPRS Jam Gadang Bukittinggi faces several problems, including limited digital services, inadequate physical facilities, and a decline in the number of customers, indicating that its services have not fully met customer expectations. This study aimed to analyze strategies for improving service quality and identify the factors influencing it based on the dimensions of tangibles, reliability, responsiveness, assurance, and empathy. The study employed a qualitative approach with a descriptive design. Informants were selected through purposive sampling and consisted of management personnel, operational staff, and four customers selected based on their experience using the services of PT BPRS Jam Gadang Bukittinggi. Data were collected through direct observation, interviews, and documentation and were subsequently analyzed qualitatively to obtain an in-depth understanding of service conditions. The results showed that service quality was not yet optimal, although various improvement efforts had been undertaken. In the tangibles dimension, service facilities were not fully adequate and were not yet supported by modern banking technology. In the reliability and responsiveness dimensions, the delivery of information and employee responses remained inconsistent, whereas in the assurance and empathy dimensions, challenges persisted in building trust and providing individualized attention to customers. These findings confirm that improving service quality requires an integrated strategy involving infrastructure improvement, digital service development, and enhancement of human resource competencies. This study contributes to the development of research on service quality in Islamic banking and provides practical implications for PT BPRS Jam Gadang Bukittinggi in improving service efficiency, customer satisfaction, and institutional competitiveness.